2018
DOI: 10.3390/ijerph15040606
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Orthodontic Cement Containing Quaternary Ammonium Polyethylenimine Nanoparticles Adjacent to Orthodontic Brackets

Abstract: Enamel demineralization is a common problem found in patients using orthodontic devices, such as orthodontic braces. It was found that Streptoccocus mutans growth increases adjacent to orthodontic devices, which may result in caries development. Incorporated antibacterial quaternary ammonium polyethylenimine (QPEI) nanoparticles were previously shown to be highly efficacious against various bacteria. Combining antibacterial materials in orthodontic cement may be advantageous to prevent bacterial outgrowth adja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The modification of the NeoBond (Dentsply) orthodontic cement with 1.5 wt.% QA-PEI nanoparticles resulted in the complete inhibition of S. mutans bacterial growth and did not change material biocompatibility [94]. Another study showed that the same orthodontic cement, enriched with 1 wt.% QA-PEI nanoparticles, reduced and inhibited the bacterial growth of S. mutans and L. casei in the oral biofilm adjacent to bonded brackets by approximately 90% [120]. Additionally, the bacterial biomass around orthodontic brackets was reduced by more than 40%.…”
Section: Qa-pei Nanoparticles In Other Dental Materialsmentioning
confidence: 99%
“…The modification of the NeoBond (Dentsply) orthodontic cement with 1.5 wt.% QA-PEI nanoparticles resulted in the complete inhibition of S. mutans bacterial growth and did not change material biocompatibility [94]. Another study showed that the same orthodontic cement, enriched with 1 wt.% QA-PEI nanoparticles, reduced and inhibited the bacterial growth of S. mutans and L. casei in the oral biofilm adjacent to bonded brackets by approximately 90% [120]. Additionally, the bacterial biomass around orthodontic brackets was reduced by more than 40%.…”
Section: Qa-pei Nanoparticles In Other Dental Materialsmentioning
confidence: 99%
“…6 These include, quaternary ammonium dimethacrylate, quaternary ammonium polyethyleneimine nanoparticles, chlorhexidine and triclosan etc. 7 Silver exhibits broad spectrum activity against fungi, bacteria and certain viruses. In order to reduce surface microbial biofilm, silver nanoparticles (AgNPs) are being applied as antimicrobials in biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the chitosan nanoparticles used had a deacetylation degree of >85%, while the chitosan nanoparticles used in this study had a deacetylation degree of 75%. 9 According to Younes, the higher the degree of deacetylation, the higher the effectiveness of the bacteria. This happens because more acetyl groups are released and operate as free amine groups that can bind to bacterial cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…6 Nanoparticle materials that can be used in the field of dentistry, especially orthodontic adhesive resins, are comprised of inorganic and organic nanoparticle material. [7][8][9][10] One inorganic nanoparticle material that may be incorporated to orthodontic adhesive resins is titanium dioxide due to its transparent color which may not interfere with the color of resin. The addition of titanium dioxide is reported to possess antibacterial property.…”
Section: Introductionmentioning
confidence: 99%